Perioperative and oncologic outcomes of robot-assisted vs. open radical cystectomy in bladder cancer patients: A comparison of two high-volume referral centers. Issue 11 (November 2016) - Gandaglia, G.; Karl, A.; Novara, G.; de Groote, R.; Buchner, A.; D'Hondt, F.; Montorsi, F.; Stief, C.; Mottrie, A.; Gratzke, C.
Abstract: Objectives: To examine perioperative and oncologic outcomes of open (ORC) and robot-assisted radical cystectomy (RARC) in bladder cancer (BCa) patients. Methods and materials: 368 consecutive patients with cT1-4 M0 BCa treated at two high-volume European centers between 2004 and 2013 were evaluated. Data on complications, operative time, blood loss, postoperative transfusion, reoperation, length of stay (LOS), positive margins, recurrence, cancer-specific mortality (CSM), and overall survival were evaluated. Uni- and multivariable regression analyses tested the impact of the surgical approach on perioperative and oncologic outcomes. Results: Overall, 230 (62.5%) and 138 (37.5%) patients were treated with ORC and RARC. In multivariable analyses RARC patients had higher odds of prolonged operative time and low-grade complications (all P ≤ 0.001). Patients treated with ORC had higher odds of blood loss >500 ml and prolonged LOS (all P ≤ 0.03). No differences were observed in high-grade complications and positive margins (all P ≥ 0.06). No differences were observed in 5-year recurrence-free and CSM-free survival rates between patients treated with ORC vs. RARC (57.1 vs. 54.2% and 61.9 vs. 73.5%; all P ≥ 0.3). This was confirmed in multivariable analyses, where the surgical approach was not associated with the risk of recurrence and CSM (all P ≥ 0.1). Conclusions: Although ORC might be associated with a shorter operative time, RARC led to lower blood loss and shorter LOS. No differences exist in high-grade complications and positive margins. RARC and ORC provide similar oncologic control.